2020
DOI: 10.1007/s00167-020-06263-3
|View full text |Cite
|
Sign up to set email alerts
|

Treatment type may influence degree of post-dislocation shoulder osteoarthritis: a systematic review and meta-analysis

Abstract: Purpose Age at primary dislocation, recurrence, and glenoid bone loss are associated with development of osteoarthritis (OA). However, an overview of OA following traumatic anterior shoulder instability is lacking and it is unclear to what degree type of surgery is associated with development of OA in comparison to non-operative treatment. The aim of this study was to determine the degree of OA at long-term follow-up after non-operative and operative treatments for patients with anterior shoulder instability. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…Furthermore, over 95% of shoulder dislocations occur in the anterior direction, in contrast to the less frequently occurring posterior and inferior dislocations [ 50 , 59 ]. Shoulder dislocations limit patients in activities of daily living and sports and are associated with development of osteoarthritis [ 51 , 60 ]. In addition, recurrent instability includes high social costs and performing operative treatment following a first-time dislocations is demonstrated to be cost-effective [ 9 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, over 95% of shoulder dislocations occur in the anterior direction, in contrast to the less frequently occurring posterior and inferior dislocations [ 50 , 59 ]. Shoulder dislocations limit patients in activities of daily living and sports and are associated with development of osteoarthritis [ 51 , 60 ]. In addition, recurrent instability includes high social costs and performing operative treatment following a first-time dislocations is demonstrated to be cost-effective [ 9 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…Non-operative treatment of shoulder dislocation arthropathy should be the first step of management. Classic studies have shown similar OA proportions between non-operative and operative treatment at any point of follow up [ 35 ]. There is no evidence of significant benefit in using non-steroidal anti-inflammatory drugs (oral or topic) to treat shoulder pain.…”
Section: Treatment Options and Resultsmentioning
confidence: 99%
“…Comparing the rate of OA after Bankart and Bristow–Latarjet procedures after ten years of follow up Hovelius found a higher incidence after the Bankart procedure (16 of 26) than after the Bristow–Latarjet procedure (9 of 30). A recent meta-analysis suggests that the Latarjet procedure has a lower OA degree than other treatments, including non-operative treatment [ 35 ].…”
Section: Causes and Prognostic Factorsmentioning
confidence: 99%
“…Moreover, a recent meta-analysis [ 56 ] even showed that Latarjet procedure provides a lower degree of OA compared to the other treatments, both operative and non-operative.…”
Section: Discussionmentioning
confidence: 99%